The Body, the Earth. The Participation of Disabled People in the Environmental Discourse - Montalti , Chiara (Journal of Ecohumanism, 2024)
The essay aims to challenge the position of disability within environmental analyses and activism. I explore the broad environmentally focused discourse: namely, I will refer to the sociocultural texts, ideologies and worldviews that are implicated in the accounts of the environmental crises provoked by climate change. Which subjects have a voice, and which tend to remain in the background? Should the environmental discourse be understood as â€œneutralâ€, because of what is at stake on a global level? I will consider these concerns through the lens of disability. Firstly, I will explore how disability usually functions as a signpost for two issues: (I) disabled people are represented as victims of the precarious living conditions exacerbated by climate change and environmental devastation and, (II) disability is employed as a cautionary tale regarding the outcomes of environmental devastation. Secondly, I will examine a performance called â€œThe Mermaidâ€, by Australian artist Hanna Cormick, which addresses the intersection of disability and environmental damage. I will read Cormickâ€™s work through Donna Harawayâ€™s concept of witness, proposing an update of environmental discourses. The aim behind this new framework is to positively situate disabled people: they should play an active role in addressing toxicity, capitalist extractivism and the entangled nature between the human subject and the environment.